A bi-functional catalyst for oxygen reduction and oxygen evolution reactions from used baby diapers: α-Fe2O3 wrapped in P and S dual doped graphitic carbon. Issue 69 (6th July 2016) - Zhao, Hong; Wang, Jian; Chen, Chi; Chen, Dengjie; Gao, Yang; Saccoccio, Mattia; Ciucci, Francesco
Abstract : The development of energy conversion and storage devices and the disposal of solid waste represent two major challenges for environmental sustainability. Abstract : The development of energy conversion and storage devices and the disposal of solid waste represent two major challenges for environmental sustainability. The development of many key sustainable energy technologies relies on fast oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) kinetics. However, both reactions are sluggish. In the present work, we address these two issues synergistically by fabricating Fe2 O3 wrapped in P and S dual-doped graphitized carbon (Fe2 O3 /P–S-CG) from soiled baby diapers, whose disposal and recycling are beneficial to the environment. Electrochemical tests revealed that Fe2 O3 /P–S-GC has a significant catalytic activity towards both the ORR and OER in 0.1 M KOH. In particular, the difference between the ORR potential at 3 mA cm −2 and the OER potential at 10 mA cm −2 is as small as ∼0.86 V. This value is comparable to that of commercial precious metal-based catalysts. In addition, Fe2 O3 /P–S-GC exhibits a favorable catalytic durability, making it a promising bi-functional non-precious catalyst for the ORR and OER.